2014
DOI: 10.4244/eijv9i12a237
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, predictive factors and haemodynamic consequences of acute stent recoil following transcatheter aortic valve implantation with a balloon-expandable valve

Abstract: Aims: The elastic behaviour (acute recoil) of a valve prosthesis stent following transcatheter aortic valve implantation (TAVI) is unknown. This study sought to determine the occurrence, severity, predictive factors and haemodynamic consequences of acute recoil following TAVI. Methods and results:A prospective angiographic analysis of the stent frame dimensions in 111 consecutive patients who underwent TAVI with a balloon-expandable valve (36 Edwards SAPIEN; 75 SAPIEN XT) was performed. Acute recoil was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Studies have shown an average 3.75–5.18% of acute recoil associated with the SAPIEN XT valve depending on the valve size or the study [7, 8]. This case report shows late recoil as the likely mechanism for progression of PVL during follow-up after a 26-mm SAPIEN XT implantation and in summation shows 7.07–9.25% of acute plus late recoil at different valve levels at 1 year of follow-up.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Studies have shown an average 3.75–5.18% of acute recoil associated with the SAPIEN XT valve depending on the valve size or the study [7, 8]. This case report shows late recoil as the likely mechanism for progression of PVL during follow-up after a 26-mm SAPIEN XT implantation and in summation shows 7.07–9.25% of acute plus late recoil at different valve levels at 1 year of follow-up.…”
Section: Resultsmentioning
confidence: 62%
“…Both studies only included the first-generation SAPIEN valve and the second-generation SAPIEN XT valve, and both reported higher degree of acute recoil with the SAPIEN XT valve [7, 8]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that complete or underexpansion of THV may also be related to the annular size, extent of aortic valve calcification, THV stent recoil, or inadequate THV balloon expansion (under-filling or over-filling delivery balloon volume and short or long duration of balloon expansion). 18 , 19 However, our study showed that aortic valve calcium distribution and LVOT calcium were not significantly different between the S3 and the S-XT groups ( Tables 2 and 6 ), suggesting the critical difference to be device driven.…”
Section: Discussionmentioning
confidence: 61%
“…The correlation between expansion area of the THV and delivery balloon volume on prior-generation, balloon-expandable THV (S-XT) has been described in one other study. Barbanti et al 18 analysed 134 patients with severe aortic stenosis who underwent TAVI with the S-XT. Nominally filled delivery balloon volume resulted in a prosthesis cross-sectional CT area that correlated well with the expected THV area.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that excessive oversizing and XT valve both predicted a larger degree of stent recoil. 21) Accordingly, for XT prosthesis, there is an increased calcified space that remains between the aortic annular wall and the prosthesis. This space allows blood to regurgitate through incomplete apposition.…”
Section: Discussionmentioning
confidence: 99%